Multilingualism in Bugis Language Context: A Case Study on English Language Teaching Interactions - Andi Husni A. Zainuddin; Masruddin Masruddin; Magfirah Thayyib (Faculty of Education and Teacher Training of UIN Palopo, 2024)
This study explores the intricate dynamics of multilingualism within the Bugis language context and its impact on English Language Teaching (ELT) at UPT SP SDN 251 Pae-Pae. With a focus on the Bugis community in Indonesia, the research delves into the complexities of language interaction in daily life and the teaching process. The Bugis language, embedded in rich cultural heritage, coexists with Indonesian and English, presenting a unique multilingual tapestry. The study employs a qualitative case study approach, including in-depth interviews with an English teacher. Findings reveal variations in language use within the family, community, and classroom contexts. Challenges arise in understanding nuanced meanings between languages, particularly in higher grades. The English teacher supports a multilingualism approach in teaching, emphasizing its role in enhancing students' adaptability and cultural sensitivity. The study contributes valuable insights to the broader discourse on language education and multilingualism in a globalized world, affirming the significance of a multilingual pedagogical approach in preparing students for diverse communication scenarios.